Knowledge transfer model in collective intelligence theory - Gunasekaran S.S.; Mostafa S.A.; Ahmad M.S. (Springer Verlag, 2023)
Decision making; Decision theory; Group theory; Knowledge management; Multi agent systems; Collaboration; Collective intelligences; Communication process; Knowledge transfer model; Multi-agent environment; Intelligent agents